Comprehensive chemical and bioactive investigation of Chinese peony flower: a case of valorization of by-products as a new food ingredient from Chinese herb - Peng, Meng-ling; Gong, Ming-Jiong; Zhang, Jing; Gadetskaya, Anastassiya V.; Liang, Qian-Wen; He, Pei-Wen; Qiu, Xiao-Hui; Huang, Zhi-Hai; Xu, Wen (Frontiers in Plant Science, 2025)
IntroductionIn the present study, the flower of Chinese peony (CPF), major waste by-product of Chinese Herb Radix paeoniae, was comprehensively investigated for the first time.MethodsA validated UHPLC Orbitrap Mass spectrometry combined a three-levels characterization strategy were used to analyze CPF samples from four representative cultivars. The anti-inflammatory and antioxidant activities were analyzed using RAW264.7 cells, and DPPH, ABTS, FRAP, and ORAC antioxidant assays.ResultsA total of 150 chemical components were identified in CPF, among them, more than 50 components were reported from this species for the first time, with potential new chemicals reported. 67 quantified or semi-quantified targeted metabolomics analysis indicated a clear distinction between flower parts and four cultivars. CPF demonstrated significant antioxidant activities and displayed anti-inflammatory effects by reducing nitric oxide, IL-6, and TNF-a release in LPS-induced macrophages. Correlation analysis highlighted a strong positive correlation between total phenolic content and DPPH ABTS, and FRAP antioxidant activities.DiscussionThe present study is the first to comprehensively investigate the chemical profile and bioactivities of CPF, which provide insights into further understanding of its health-promoting potential.